2016
DOI: 10.7869/tg.314
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Interventions in Acute Necrotizing Pancreatitis

Abstract: Acute pancreatitis (AP) is a disease of varying severity with acute necrotizing pancreatitis (ANP) being the severe form of AP. ANP needs multidisciplinary management and is associated with significant mortality and morbidity. Local complications of ANP viz. acute necrotic collections (ANC) and walled off pancreatic necrosis (WOPN) need intervention if they are associated with symptoms, sepsis or worsening organ failure. As surgery is associated with higher morbidity and mortality, there is paradigm shift in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Using an acute pancreatitis (AP) mouse model, the same research group confirmed the correlations between the gut microbiota burden and AP severity [94]. ANP is a severe form of AP [37]. In other studies, an E. coli MG1655 mono‐colonized ANP rat model showed more severe pancreatic injury in comparison to a normal ANP rat model with significant upregulation of the TLR‐4‐mitogen‐activated protein pathway and activation of the endoplasmic reticulum stress pathway in intestinal epithelial cells [38].…”
Section: Pancreatic‐intestine Axis In Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an acute pancreatitis (AP) mouse model, the same research group confirmed the correlations between the gut microbiota burden and AP severity [94]. ANP is a severe form of AP [37]. In other studies, an E. coli MG1655 mono‐colonized ANP rat model showed more severe pancreatic injury in comparison to a normal ANP rat model with significant upregulation of the TLR‐4‐mitogen‐activated protein pathway and activation of the endoplasmic reticulum stress pathway in intestinal epithelial cells [38].…”
Section: Pancreatic‐intestine Axis In Inflammationmentioning
confidence: 99%
“…Furthermore, bacteria can translocate to the pancreas under pathological conditions [35,36]. With the increase in intestinal microbes and by compromising the epithelial barrier function, pancreatitis is more severe and may lead to acute necrotizing pancreatitis (ANP) [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Drainage catheter is then inserted along the guidewire after adequate dilatation of the tract. Trocar technique employs advancing a co-axial combination of a sharp stylet, stiffening cannula, and the draining catheter[ 29 ]. Seldinger technique is more useful for deep collections but is more time-consuming as it involves multiple steps.…”
Section: Percutaneous Catheter Drainagementioning
confidence: 99%
“…Seldinger technique is more useful for deep collections but is more time-consuming as it involves multiple steps. Trocar technique is useful in large and superficial collections but is more painful[ 29 ].…”
Section: Percutaneous Catheter Drainagementioning
confidence: 99%
See 1 more Smart Citation